Examination of the physical profiles of physically handicapped female badminton players - Mehmet Fatih Yüksel (Türk Spor ve Egzersiz Dergisi)
This research was conducted to determine physical characteristics of physically handicapped women badminton players and to examine the effects of badminton sport on the physical characteristics of physically handicapped women. A total of 43 women including physically handicapped badminton players (n= 20) and control group consisting of physically handicapped (n= 23) participated voluntarily to the researh. In accordance with the obstacle classification determined by the International Physically Handicappeds Badminton Federation, handicapped female badminton players were composed of two groups including SL-3, SL-4, SU-5 (standing players, n= 11) and WH-1, WH-2 (wheelchair players, n= 9). In control groups, disabled persons with inactive lifestyle (standing, n= 13 and wheelchair, n= 10) were included in the study. In order to identify the physical characteristics of the participants; stature, weight, BMI, upper extremity length (arm-forearm-hand), circumference (arm-forearm), flexibility, balance, modified sit-ups, modified abdominal endurance, hand grip strength, plate tapping and modified push-up tests were made. SPSS 21.0 program was used in the analysis of the data and differences between the groups were determined by Mann-Whitney U test. Significancy level was considered as p lt;0.05. In the result of the study, significant differences were determined according to control groups In the parameters of weight, BMI, balance, modified sit-ups, hand grip strength, plate tapping and modified push-up parameters of female disabled badminton players playing standing and in the parameters of weight, BMI, flexibility, modified sit-ups, modified abdominal endurance, and plate tapping of wheelchair badminton players. As a result, it is determined that badminton sports improve the physical properties of physically handicapped women. In addition, it can be said that badminton sport can have a positive contribution in the process of raising the physical fitness levels of persons with disabilities who are deprived of some physical capacity and adaptation to life conditions.